The Determinants Affecting the Customs Risk Management (Crm) in Dong Nai Province - Thi Bich Thuy; Tran Thi My Huong, Nguyen (British Journal of Marketing Studies, 2018)
In modern customs management, the application of risk management (RM) is considered to be important. The customs risk management can identify the key areas of potential high risk of smuggling, trade fraud, tax evasion and budget deficits so that customs administrations can take effective preventive measures. At the same time, it will create favorable conditions for enterprises to obey customs law. The objective of this study is to find out various factors affecting the customs risk management (CRM) in Dong Nai province. Data surveyed 200 managers of enterprises related to Dong Nai customs. The surveying time is from 9/2017 to 3/2018. Data processed by SPSS 20.0 and method used by the multiple linear regression analysis. The research results showed there are three key factors that affecting the customs risk management (CRM) in Dong Nai province with level significance 5 percent.